Kekudusan dan Kemurnian:: Strategi Integrasi pada Komunitas Israel Pascapembuangan dalam Tradisi Imam Imamat 19 dan Ezra 6 - Duma Indah Sinaga (Sekolah Tinggi Teologi Injil Bhakti Caraka, 2023)
This paper seeks to analyze two integration strategies of the Israelites with other nation in two post-exilic priestly traditions, namely Leviticus 19 and Ezra 6. In this integration effort, Leviticus 19 uses the theme of holiness while Ezra 6 uses the theme of purity. This paper will show that although these are mutually supportive and not contradictory terms, there are extreme differences in usage in Leviticus 19 and Ezra 6. This extreme usage leads to a very different nature of integration between Leviticus 19 and Ezra 6. Leviticus 19 promotes ethically-based integration, while Ezra 6 promotes cult-based integration. This fundamental difference at the same time indicates a change or development of thought in the priestly tradition. Using a literature based qualitative research, this paper will show two integration strategies in the two post-exilic priestly tradition.